Degradation of chemical oxygen demand, suspended solids and ammoniacal nitrogen from sewage by sweet potato peel coagulant under the influence of pH - Nur Shaylinda, Mohd Zin; Jismi, N M M N; Nazari, A N A; Akbar, N A; Mohd Fakhrurrazi, Ishak; Talib, S H A; Mohd-Salleh, S N A (IOP Publishing Ltd., 2024)
Coagulation is a common treatment stage included in conventional sewage treatment. Various chemical, synthetic and natural coagulants in the form of single, dual and composite were applied in this treatment stage. However, the application of natural coagulants made from food waste is still uncommon. Thus, this study compares the ability of sweet potato peel as a composite coagulant (PACSPP), dual coagulant (PAC+SPP) and single coagulant (SPP) under the influence of pH in removing chemical oxygen demand (COD), suspended solids (SS) and ammoniacal nitrogen (AN) from sewage wastewater. Raw sewage sample before primary treatment was collected from University Tun Hussein Onn Sewage Treatment plant by using grab sampling method. Optimization study was conducted by using jar tester. At the optimum condition of PACSPP (pH 7), the percentage removal of COD, SS and AN was 54%, 95% and 39%. While a single SPP coagulant, at its optimal pH of 9, achieved 24%, 16% and 17% removals of COD, SS and AN, respectively. Meanwhile, optimisation of dual coagulant (pH 9) demonstrated 39%, 73% and 42% removals of COD, SS and AN, respectively. Thus, SPP, as a composite coagulant, outperformed the dual and single coagulant of SPP.